Associations between psychosocial work environment factors with work engagement and burnout in nursing - Žiedelis, Arūnas (Psichologija, 2019)
The psychosocial work environment (i.e., job demands and resources) is a significant determinant of nurses’ health and motivation; yet, despite the close associations between specific work environment factors, various frameworks suggest different aspects as the most important among the rest. Having in mind the assumption that a more abstract level of analysis might be equally relevant for understanding the work environment and predicting significant outcomes, the aim of this study was to discern the latent factors of nursing work environment and to evaluate their significance in predicting nurses’ work engagement and exhaustion. Two hundred eleven nurses participated in a two-wave time-lagged survey (ΔT = 8 months). In this survey, 1 Expanded Nursing Stress Scale and several subscales of the Work Design Questionnaire were used to measure main job demands and resources in nursing. At that time, 2 participants were asked to fill out an Utrecht Work Engagement Scale and Copenhagen Burnout Inventory. Exploratory factor analysis (EFA) and hierarchical regression analysis were used for analyzing the data. The EFA results revealed that two factors can be discerned, each related to main job demands and resources accordingly. Based on these results, the aggregated indexes of job demands and resources were calculated. A linear regression analysis showed that these indexes predicted nurses’ work engagement and exhaustion no worse than specific factors, despite the loss of variance due to aggregation. Practical implications of such conclusions are also discussed in the article.